Deterioration mechanism of insulated circuit substrates in thermoelectric modules operating at medium–high temperatures in air atmosphere. (February 2021) - Arai, Koya; Romanjek, Krunoslav; Nishikawa, Kimihito; Nishimoto, Shuji; Komasaki, Masahito; Nagatomo, Yoshiyuki; Kuromitsu, Yoshirou
Highlights: TE modules were fabricated on DBC substrates with Ni-Au or Ag plating and Ag bonding paste. The thermal durability tests were performed in air atmosphere. Internal resistance of the TE module with Ni-plated layer was larger increased than one without Ni. Small voids in the Ag bonding paste layer had become large with thermal cycling on only the hot side. The Ni in the Ni/Au-plating layer in the TE module e was oxidized on only the hot side. Abstract: In this paper, the power generation characteristics for the thermoelectric modules operating at medium–high temperatures in air atmosphere are measured, and the effects of deterioration of insulated circuit substrates and the bonding layers are measured and analyzed. Thermoelectric modules with a π-structure were fabricated on direct bonded copper (DBC) substrates with Ni-Au or Ag plating and Ag bonding paste for mounting the thermoelectric legs, and their medium–high temperature durability was evaluated. In durability tests, the thermal cycling was carried 100 cycles (cold side: Tc = 80 °C; hot side: Th = 150 °C ⇔ 450 °C) in ambient air. The power generation characteristics of the TE modules were measured when the hot-side temperature was 450 °C in ambient air, and the value of internal resistance of the TE module was calculated. After the durability test, cross-sections of the modules were prepared and analyzed by scanning electron microscopy (SEM) and electron probe microanalysis (EPMA). Comparing the SEM images of the hot and cold sides after thermal cycling revealed that small voids in the Ag bonding paste layer had become large and that the growth of Ag microcrystal grains progressed with thermal cycling. Moreover, the EPMA results revealed that Ni in the module with the Ni-Au-plated DBC substrate was oxidized on the hot side. An approximately 0.3-μm-thick nickel oxide layer formed at the interface between the Ni plating layer and the sintered Ag bonding paste layer. After thermal cycling, the percent increase in resistance of the modules with a Ni-Au-plated DBC substrate became larger than that of the Ag-plated DBC substrate because of this Ni oxidation. Taken together, these results suggest that Ni was oxidized by atmospheric oxygen, and that the internal resistance of the module with a Ni-Au-plated DBC substrate was greatly increased because of the Ni oxidation.